2017
DOI: 10.1097/md.0000000000007826
|View full text |Cite
|
Sign up to set email alerts
|

Altered default mode network configuration in posttraumatic stress disorder after earthquake

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
4
0
1
Order By: Relevance
“…In addition, PTSD severity (and specifically re‐experiencing symptoms) was negatively correlated with the strength of connectivity between PCC (a key DMN node) and anterior MTG, proposed to be part of a DMN subsystem (Uddin, Kelly, Biswal, Castellanos, & Milham, 2009; Xu et al, 2015). This finding adds to a growing body of evidence suggesting lower within‐DMN connectivity in patients with PTSD compared with controls (Akiki et al, 2018; Bluhm et al, 2009; Lazarov et al, 2017; Miller et al, 2017; Olson et al, 2019; Shang et al, 2014; Viard et al, 2019; Zhang et al, 2017). Since DMN is linked to stimulus‐independent and internally focused thought, this finding could represent general disruption in self‐referential thought in patients with PTSD.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, PTSD severity (and specifically re‐experiencing symptoms) was negatively correlated with the strength of connectivity between PCC (a key DMN node) and anterior MTG, proposed to be part of a DMN subsystem (Uddin, Kelly, Biswal, Castellanos, & Milham, 2009; Xu et al, 2015). This finding adds to a growing body of evidence suggesting lower within‐DMN connectivity in patients with PTSD compared with controls (Akiki et al, 2018; Bluhm et al, 2009; Lazarov et al, 2017; Miller et al, 2017; Olson et al, 2019; Shang et al, 2014; Viard et al, 2019; Zhang et al, 2017). Since DMN is linked to stimulus‐independent and internally focused thought, this finding could represent general disruption in self‐referential thought in patients with PTSD.…”
Section: Discussionsupporting
confidence: 55%
“…Evidence from functional magnetic resonance imaging (fMRI) studies using resting‐state functional connectivity (rsFC) suggests disrupted connectivity in the Default‐Mode Network (DMN; associated with internally focused thought and autobiographical memory) and Salience Network (SN; responsible for detecting and orienting to salient stimuli) in individuals with PTSD (Liberzon & Abelson, 2016). Specifically, PTSD has been associated with (1) greater within‐SN connectivity (Abdallah et al, 2019; Brown et al, 2014; Rabinak et al, 2011; Sripada, King, Garfinkel, et al, 2012), (2) lower within‐DMN connectivity (Akiki et al, 2018; Bluhm et al, 2009; Lazarov, Zhu, Suarez‐Jimenez, Rutherford, & Neria, 2017; Miller et al, 2017; Olson, Kaiser, Pizzagalli, Rauch, & Rosso, 2019; Shang et al, 2014; Viard et al, 2019; Zhang et al, 2017), and (3) greater cross‐network SN–DMN connectivity—often called desegregation (Brown et al, 2014; Lanius et al, 2010; Sripada, King, Garfinkel, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our PTSD cohort showed altered mean connectivity compared with HC in the same connectome features that characterised mTBI. This is consistent with previous studies that have also found alterations in intrinsic connectivity in PTSD compared with controls (Akiki et al, 2018;Breukelaar et al, 2021;Jung et al, 2016;Lei et al, 2015;Rabinak et al, 2011;Sripada et al, 2012;Zhang et al, 2017), particularly in the networks found in our study. There were, however, no differences in mean connectivity between mTBI and PTSD in all features that characterised mTBI from controls.…”
Section: Discussionsupporting
confidence: 94%
“…Studies of functional brain connectivity at rest show similar results in PTSD ( Akiki et al, 2017 ; Etkin et al, 2011 ; Etkin and Wager, 2007 ; Fitzgerald et al, 2018 ; Koch et al, 2016 ; Patel et al, 2012 ; Sartory et al, 2013 ; Schulze et al, 2019 ; Thome et al, 2020 ; Wang et al, 2016 ). These studies show altered function/connectivity in the hippocampus ( Abdallah et al, 2017 ; Admon et al, 2013 ; Bluhm et al, 2009 ; Chen and Etkin, 2013 ; Chen et al, 2019 ; Jin et al, 2014 ; Lazarov et al, 2017 ; Malivoire et al, 2018 ; Metz et al, 2019 ; Miller et al, 2017a ; Rabellino et al, 2018a , 2018b ; Stevens et al, 2014 ; Zhang et al, 2017 ), parahippocampus ( Jin et al, 2014 ; Misaki et al, 2018 ), insula ( Birn et al, 2014 ; Etkin et al, 2019 ; Harricharan et al, 2020 ; Ke et al, 2018 ; Koch et al, 2016 ; Liu et al, 2017 ; Nicholson et al, 2020 ; Sripada et al, 2012a ; Tursich et al, 2015 ; Vanasse et al, 2019 ; Zhang et al, 2016b ), amygdala ( Admon et al, 2009 ; Barredo et al, 2018 ; Disner et al, 2018 ; Jin et al, 2014 ; Koch et al, 2016 ; Nicholson et al, 2019 , 2017 ; Satterthwaite et al, 2016 ; Simmons et al, 2008 ; Stevens et al, 2013 ; Sun et al, 2020 ; Weng et al, 2019 ; Yan et al, 2013 ; Yuan et al, 2019 ; Zhang et al, 2016a ; Zhu et al, 2017 ), medial prefrontal cortex ( Akiki et al, 2018 ; Amad et al, 2019 ; Birn et al, 2014 ;…”
Section: Introductionunclassified